2017
DOI: 10.4018/ijdet.2017070105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Peer Interaction Effects on Learning Achievement in a Social Learning Platform Based on Social Network Analysis

Abstract: The benefits of social learning have been recognized by existing research. To explore knowledge distribution in social learning and its effects on learning achievement, we developed a social learning platform and explored students' behaviors of peer interactions by the proposed algorithms based on social network analysis. An empirical study was also conducted on a college course to investigate the correlation between peer interaction and learning achievement. The experiment results show that the students who t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These perceptions valued two differentiating e-learning methodology features: on the one hand, having to create collaborative environments among students to promote suitable T/L processes. Previous studies have shown that peer interaction is essential for online learning [88][89][90][91][92][93]. Moreover, [94] found that peer interaction is not only important for student satisfaction, with a well laid-out design and interaction with teachers, but active discussion among peers was also relevant.…”
Section: Benefitsmentioning
confidence: 94%
“…These perceptions valued two differentiating e-learning methodology features: on the one hand, having to create collaborative environments among students to promote suitable T/L processes. Previous studies have shown that peer interaction is essential for online learning [88][89][90][91][92][93]. Moreover, [94] found that peer interaction is not only important for student satisfaction, with a well laid-out design and interaction with teachers, but active discussion among peers was also relevant.…”
Section: Benefitsmentioning
confidence: 94%
“…This is not unexpected, as online lessons were traditionally taught in an online manner with limited room for discussion and coincides with previous studies. ,, Furthermore, 85% express their hesitance in asking questions during tutorial sessions, which could easily translate to shyness and a lack of proactive engagement in other social platforms as well. This lack of engagement, which then leads to a lack of peer interactions is one that hampers the formation of learning communities significantly, having detrimental effects on student learning. , …”
Section: Discussionmentioning
confidence: 99%
“…This lack of engagement, which then leads to a lack of peer interactions is one that hampers the formation of learning communities significantly, having detrimental effects on student learning. [10][11][12][13][14]30 As a solution to the problem of student shyness and reluctance in participation, both faculty and student tutors actively directed questions to the student body. For instance, if a question was asked to the lecturer personally, via email or messaging to the lecturer or peer tutor, students were directed to post the question publicly, allowing other students to discuss and propose solutions.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid learning, which is in line with the national strategy of information-based education, can promote the autonomous learning ability, cooperative learning ability, and personalized development of students [7][8][9][10][11]. Thanks to the quick proliferation of online learning platforms in schools at all levels, the online learning of hybrid learning is blessed with a strong technical support [12][13][14][15]. Whether online learning or offline learning, the learning quality hinges on the good learning behaviors and learning participation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%